Cobalt (II)‐catalyzed oxidation of 2‐aryl benzoic acids to access biaryl lactones. (13th July 2022) - Chao, Mianran; Wang, Hongyan; Zhang, Haixing; Zhong, Fubi; Luo, Zhen; Wu, Fengyun; Sun, Feiyang; Jiang, Jiaojiao; He, Xuexue; Zhang, Shumiao; Gong, Peiwei; Wang, Bin; et al.
Abstract : Cobalt/peroxymonosulfate (Co/PMS) system is an efficient advanced oxidation process (AOP) for degradation of organic pollutants in wastewater, however, has limitations in organic synthesis. Herein, we employ a Co/PMS system to the preparation of biaryl lactones by the valorization of 2‐aryl aromatic acids via intramolecular O‐H/C‐X oxidative coupling. This system exhibits intriguing advantages, such as non‐noble metal catalyst, common oxidant, mild condition, easy workup and product isolation. Mechanism studies, including the radical quenching experiments and multiple probe substrates, suggest that a high‐valent cobalt‐oxo intermediate should be one major active species. Meanwhile, both persulfate radical anion (SO4 − ) and hydroxyl radical (OH) are present in the process and contribute to the organic reaction. This work not only expands the synthetic application of Co/Oxone system beyond environmental fields, but also provides more active intermediates than generally‐accepted SO4 − in the known metal‐based AOPs. Abstract : A catalytic method for the biaryl lactones has been developed under mild conditions using the earth‐abundant cobalt salts and a common peroxymonosulfate oxidant. Not only the generally‐accepted persulfate radical anion, but also high‐valent cobalt‐oxo and hydroxyl radical were proposed as the active species.